Cobalt-Catalyzed Glaser-type Homocoupling Reaction - Han, Jun-Fa; Guo, Peng; Chen, Lin; Ye, Ke-Yin (Synthesis, 2022)
A highly efficient cobalt-catalyzed homocoupling of terminal alkynes with di-tert-butyldiaziridinone as the oxidant has been developed. The protocol tolerates a wide array of terminal alkynes, both activated and unactivated alkynes, to afford the corresponding conjugated 1,3-diynes. The mild reaction conditions further allow late-stage homocoupling of alkynes derived from complex natural products.
Keywords: Glaser coupling; cobalt; catalysis; alkynes; 1,3-diynes